Yield prediction of grassland swards using specific equations for Rising Plate Meter - Christoph Stumpe; Priska Krug; Jonas Weber; Stefan Böttinger (agricultural engineering.eu)
Accurate prediction of grassland yield is essential for efficient management and sustainable use. The Rising Plate Meter (RPM) is a device widely used in pasture management to measure the height of growth considering sward density to calculate biomass yield. This can be transferred to the use of grassland for mowing. The key is to adapt the prediction equation, which calculates the dry matter yield from the measured compressed sward height. The accuracy can be further improved by using specific prediction equations. The equations consider (1) temporal, (2) spatial and (3) sward-specific factors. To develop the specific equations, RPM measurements were carried out for two regions, the dry matter yield of the plots was determined and the data were analyzed using linear regression. The results show that the application of the specific equations improves the mean deviation from 31% (RMSE = 738 kg/ha) to 18% (RMSE = 570 kg/ha). These improvements allow farmers to predict yield already during the growing phase, providing a reliable basis for site-specific grassland management and optimizing forage production.